KI BAGUS HADIKUSUMO DAN PROBLEM RELASI AGAMA-NEGARA - Muhammad Hisyam (Jurnal Masyarakat dan Budaya, 2011)
This article examines the debates on the relationship between religion and state in the early formation of Indonesiaâ€™s independent. The formulation of this relation was firmly stated in the Jakarta Charter, as â€œthe state is based on a divinity, which obligates the Muslim to implement the shariâ€™a of Islamâ€. Thus the Jakarta Charter provides an evidence that the implementation of shariâ€™a has to involve the state. However, the charter was modified by Preparatory Committee for Indonesian Independent (PPKI), just a day after proclamation of independent, and the relationship between religion and state became unclear. During the rule of the authoritarian New Order regime the voice demanding implementation of the shariâ€™a was largely unheard, but it does not mean that the aspiration had died down. After the fall of Soeharto, and the rise of â€œReformasiâ€ order, political parties with affiliation to Islam took a strong stance to demand that omitted seven words in the Jakarta Charter were reinstated. Is the demand to restore of the seven words corresponds to the ideas of its formation during debates in the Committee for Preparatory Work for Indonesian Independent (BPUPKI) in which the document was formulated? To answer this question I investigated the minute of the Committee with special attention to Ki Bagus Hadikusumo, a Muslim representative which has well known as a vocal person in the Committee. The answer is, as I found a fact that the seven words formula in the Jakarta Charter was strongly rejected by Hadikusumo. Keywords: BPUPKI, Ki Bagus Hadikusumo, Jakarta Charter.